ANALYSIS OF THE CONTENT CAMEO PROJECT YOUTUBE VIDEO IN SUPPORTING ANTI BULLYING CAMPAIGN - Yanis, Fauziah (Universitas Islam Syekh Yusuf, 2021)
The development of communication technology which is increasingly advancing is shown by the emergence of social media such as Youtube, which is considered a platform that can be used as a means of gaining economic benefits as well as a means of communication in conveying aspirations. The Cameo Project Youtube account in its content entitled